Riesgo financiero en los microcréditos de la Cooperativa de Ahorro y Crédito Mushuc Runa Ltda. Cuidad de Riobamba-Período 2020-2022 - Pagalo Tayupanda, Cinthia Dayana (2024)
ABSTRACT: The main objective of this research study whose importance lies in the fact of knowing its internal movement through the financial analysis applied to the financial statements of the Cooperative and indicators that allow measuring the financial structure of the same, for such reason this research aims to analyze the financial risk in the microcredits of the Cooperativa de Ahorro y crédito Mushuc Runa Ltda, -The methodology used is deductive with a quantitative approach, non-experimental design, documentary and field type with a descriptive level, through the application of indicators has important significance in making timely decisions and to evaluate the financial and operational performance of the entity. The research presents a theoretical part corresponding to the theoretical foundations of financial analysis, allowing a comparative analysis of the financial situation between the proposed periods, interpreting the results obtained with the application of ratios or indicators for decision making. A diagnosis was made and then proceeded to the evaluation of the financial statements through the vertical and horizontal methods, through which the financial activity of the cooperative, the quality of its assets, savings deposits, rates of return and costs, financial cost, liquidity and signs of loan growth were known, also financial indexes were applied to measure the economic and financial profitability, The results of the application of the financial indicators show that in the last period analyzed, the loan portfolio maintains a percentage of 66.66%, which is within the parameters established in the goals (50%-80%). It is important to review and adjust the policy of granting microcredits of the cooperative to ensure that it is aligned with the needs and capacities of clients, as well as with the conditions of the economic and financial environment. Keywords: Financial Indicators, Cooperative, Solvency, Profitability, Situational Analysis, microcredit.